Hyphomycetes from Warangal-III - and S.R. REDDY, N. VENKATESHWARLU, S.M. REDDY (Indian Phytopathology, 2002)
Two new hyphomycete fungi, Oncopodium indicum on Eucalyptus lanceolatus and Triadelphia centroseptata on Cocos nucifera, are described and illustrated as new species from Warangal, Andhra Pradesh, India.